Utility of Fast Scan in Blunt Abdominopelvic Trauma Patients in Lahore District - Arifa Mobeen, Kainat Arshad, Sania Maqbool, Ruhina Mazhar, Fatima Ahmad, Fizza Aslam, Ammara Yaseen, Bilal Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To evaluate the utility of fast scan in blunt abdominopelvic trauma patients in the emergency department of tertiary care hospitals in Lahore district. Focused assessment with sonography for trauma (FAST) has been used as the first assessment in diagnosing patients with trauma in the last decade, and we have heard people questioning its authenticity and reliability, and many other things. Methodology: The study design was cross-sectional .This study was conducted at various tertiary care hospitals of Lahore, in the time duration of 3 months from January 2022 to March 2022. One hundred and six (106) patients with blunt abdominopelvic trauma were assessed by Fast scan using 2-5MHz transducer. Results: Out of 106 patients 59(55.7%) were males and 47(44.3%) were females with ages ranged between 2 to 72 years. Road traffic accidents accounted for 50% cases, 17% were due to fight while 23.6% were due to fall and 9.4% were due to assault. Of the total patients, 69.8% had negative scan while 30.2% had positive scan. Majority (6.6%) of positive scans were of splenic injury. Of all the positive scans 17% of the cases had abdominal pattern of injury while pelvic and abdominopelvic cases were 9.4% and 2.8% respectively. Practical implication: Our aim of doing this research study was to learn the benefits of performing Fast scan in BAT patients. We were able to look through possible aspects of pathology of abdomen and pelvic of traumatic patients arriving.FAST Scan is the single most valuable imaging modality in the early assessment and diagnosis of blunt abdominopelvic traumas with an aspect of safety &cost-effectiveness. Conclusion: Fast scan can be used in the initial assessment of blunt abdominopelvic trauma patients and it is verily preferred in hemodynamically stable patients. Keywords: FAST Scan, Blunt traumatic patients, Emergency department, Hemodynamic stability.